Echinococcus granulosus in buffaloes in the Northern Caucasus - B. M. Shipshev; F. I. Kishtikova; A. I. Tohaeva; I. H. Shahbiev; R. B. Bersanukaeva; H. H. Shahbiev; S. S. Mantaeva; A. M. Bittirov (Российский паразитологический журнал, 2016)
Buffaloes in Kabardino-Balkarian Republic are infected with Echinococcus granulosus at 16,7 % at intensity of infection 2–17 sp. Diameter of E. granulosus larvocysts in adult buffaloes is 3–14 sm and the cavity of bubbles is filled with a transparent liquid. Echinococcosis in buffaloes in this region proceeds with scope of an adult livestock.